A Fuzzy BWM-TOPSIS Framework for Identifying and Prioritizing Measures to Overcome Obstacles to the Regionalization of Iranian Healthcare Services - Zahra Zare; Arash Haqbin; Khalil Kalavani; Payam Shojaei (International Journal of Preventive Medicine, 2023)
Background: One of the most effective strategies to improve the access of community members to health services is to regionalize health services. The purpose of this study is to examine and prioritize measures that could help to counteract obstacles and problems in implementing the regionalization of healthcare in Iran. Methods: The study relied on a mixed research method, including qualitative and quantitative phases. First, by conducting semi-structured interviews and analyzing them through qualitative content analysis, the obstacles and measures were identified. In the quantitative phase, the obstacles identified were weighted using the fuzzy best-worst method (FBWM), and the measures were then prioritized through the fuzzy TOPSIS (FTOPSIS) method. Results: The obstacles were categorized into four main dimensions: “infrastructural,” “political,” “human resources,” and “managerial.” Among the 15 obstacles identified, “absence of performance guarantees” was the most important obstacle, while “insufficient education” was the least important obstacle to the regionalization of healthcare services in Iran. Meanwhile, the following eight measures that could help to overcome the obstacles were extracted from the interviews: “conducting a needs assessment,” “providing clinical guidelines,” “employing specialized human resources,” “reinforcing the referral system,” and “preparing electronic health records,” “enhancing education and information dissimilation,” “building executive support,” and “providing cost-effective equipment and technology.” “Employing specialized human resources” was also the most effective measure to overcome the obstacles. Conclusions: Iranian healthcare policy-makers can use the empirical findings of this investigation to accelerate the implementation of Iran's regionalization plan to improve the access of community members to healthcare services.